COVID-19 VACCINE LEGAL PROTECTION THROUGH PATENT FOR PUBLIC INTEREST - Zaki, Muhammad Reza Syariffudin; Akmal, Muhammad Farhan (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2021)
Patents are rights granted by the state to inventors for their inventions in the field of technology for a certain period of time. However, a rigid patent protection can disrupt the public interest. Therefore, the undergraduate thesis research entitled Legal Protection of Covid-19 Vaccines through Patents for Public Interest was conducted. The research conducted by juridical normative legal research methods, statutory approaches, and conceptual approaches. TRIPs Agreement, Paris Convention, Indonesian Patent Law 2016 and President Regulation No. 77/20 are the main objects of study. This research aims to answer (1) how the legal protection of the Covid-19 vaccine for the public interest, and (2) how to resolve disputes against the Covid-19 patent rights holder in Indonesia. After conducting a study, it can be concluded that patents can be implemented by the government without the authority from the patent holder in an emergency situation. In the return, a worth compensation must be given to the patent holder. If a dispute arises, it can be resolved through litigation or alternative dispute resolution (ADR), but preferably through ADR at BAM HKI. This is in purpose to empower BAM HKI, as well as to support and promote the enforcement of intellectual property rights in Indonesia.